Analysis of Kazakhstan Rock Climbing in the Form of Competitions Success: From the Origins to the Present Day - Shunko, Andrey (CV. Rayyan Dwi Bharata, 2025)
The article examines the main historical facts about the formation of rock climbing in the Republic of Kazakhstan since the establishment of the state in 1991. An assessment of the state of Kazakhstani sports as a whole was made using the example of Olympic sports. A detailed analysis of all official international performances of Kazakhstani rock climbers in adult and youth competitions was conducted. Visual tables and graphs are presented showing the negative state of sport climbing in Kazakhstan today. Key external factors influencing the development of Kazakhstani rock climbing are highlighted. The continuity of the country's general political system was demonstrated in the choice of the leadership of the Federation of Rock Climbing and Mountaineering.